Environmental and health impact assessment of Liquid Organic Hydrogen Carrier (LOHC) systems – challenges and preliminary results1. Issue 3 (5th March 2015) - Markiewicz, M.; Zhang, Y. Q.; Bösmann, A.; Brückner, N.; Thöming, J.; Wasserscheid, P.; Stolte, S.
<x xml:space="preserve">Abstract</x> This paper presents the first account on the ecotoxicological profile of some potential LOHC structures.